2007
DOI: 10.1111/j.1747-0285.2007.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐phase Synthesis of a Peptide Derivative of Thymosin alpha1 and Initial Studies on its 99mTc‐Radiolabelling

Abstract: A derivative (1) of the immunopotentiating 28-peptide thymosin alpha1 has been especially designed, so that it can be (99m)Tc-radiolabelled, and synthesized following the Fmoc solid-phase peptide synthesis approach. Derivative 1 contains the N-terminal fragment Talpha1[1-14] as a bioactive segment, at the C-terminus of which a (99m)Tc-chelating moiety consisting of N(alpha),N(alpha)-dimethylglycine, serine and cysteine is linked through the N(epsilon)-amino group of a 'bifunctional' lysine residue; the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the present work, the first reported complex (19) of a synthetic derivative of Tα1 with the ReO(V) 3+ core was studied with NMR revealing the structure 185/187 Re‐1 and the existence of two isomers ( 185/187 Re‐1 ‐ syn and 185/187 Re‐1 ‐ anti , ratio, 3:2), depending on the direction of the side chain of Ser2′ with respect to the oxygen of the ReO bond (Figure 2B). The same isomers ( 99m Tc‐1 ‐ syn and 99m Tc‐1 ‐ anti ) and in the same 3:2 ratio were also found to form by HPLC analysis when synthesis was effected at the 99m Tc tracer level.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the present work, the first reported complex (19) of a synthetic derivative of Tα1 with the ReO(V) 3+ core was studied with NMR revealing the structure 185/187 Re‐1 and the existence of two isomers ( 185/187 Re‐1 ‐ syn and 185/187 Re‐1 ‐ anti , ratio, 3:2), depending on the direction of the side chain of Ser2′ with respect to the oxygen of the ReO bond (Figure 2B). The same isomers ( 99m Tc‐1 ‐ syn and 99m Tc‐1 ‐ anti ) and in the same 3:2 ratio were also found to form by HPLC analysis when synthesis was effected at the 99m Tc tracer level.…”
Section: Discussionmentioning
confidence: 56%
“…The Ta1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] derivative was efficiently radiolabeled with 99m Tc (yield >95%) (19) and evaluated in mice with experimental inflammation induced with turpentine oil. Previous studies with 99m Tclabeled thymosin fraction 5 (TF5) in rats with experimentally induced inflammation, have shown that the accumulated radioactivity in inflamed tissue (0.07% ID ⁄ g at 4 h postinjection) was 2.3 times higher compared to the control muscle (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fragments ProTα[1-28], ProTα[50-88], ProTα[100-105], and ProTα[100-109] (Fig. 1) were in-house synthesized according to the Fmoc/ t Bu solid-phase peptide synthesis strategy and purified with semi-preparative reversed phase HPLC, following protocols previously described by our group [16, 17]. Yield of peptide synthesis was often low, due to “difficult peptide sequences” existing especially in ProTα[50-88] [18].…”
Section: Methodsmentioning
confidence: 99%
“…Tα1 for clinical use is mainly derived from animal thymus extraction or chemical synthesis [13,14], but the yield of Tα1 from these means cannot meet the increasing requirements for clinical applications. The available amount of calf or swine thymus seriously limits the yield of Tα1, and the quality of thymus‐derived Tα1 varies among different batches or manufacturers.…”
Section: Introductionmentioning
confidence: 99%